Pengaruh Pemberian Beras Merah Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi - Ahmad Zaini Arif (Universitas Nazhatut Thullab Al- Muafa Sampang, 2021)
Introduction: Hypertension is a condition that is measured by how much force the blood pressure that occurs in the arteries. A healthy blood pressure is 120/80 mmHg or by age. Hypertension if left untreated can lead to more severe complications such as heart disease and blood vessel damage. One way to normalize hypertension by eating brown rice. Objective: The purpose of this research is to know is there any effect of red rice to the reduction of blood pressure in hypertensive patients in the village of Krampon District of Torjun Sampang. Methods: The research design use a Pre Experimental one-group pre-post test desaign. This study using total sampling as many as 16 patients with hypertension. Once tabulated data that is analyzed using Mc. Nemar Test with a significance level of 0.05. Result: the study of blood pressure before administration of red yeast rice in patients with hypertension of mostly 16 hypertensive patients (100%) with high blood pressure category. Blood pressure after the administration of red rice in hypertensive patients mostly 6 patients with hypertension (37.5%) with normal blood pressure categories. While the statistical test result is no effect of Red Rice to decrease blood pressure in hypertensive patients with a significant level of 0.03 (P <0.05). Conclusions: Hypertensive patients change their lifestyle and diet, for example by exercising, eating a diet hypertension and brown rice which is very good for people with hypertension to stabilize blood pressure.